TANGGUNG JAWAB TERBATAS PEMEGANG SAHAM ATAS PAILITNYA PERSEROAN TERBATAS - Siregar, Shinju Aisuru; Tasya, Azura (Hakim: Jurnal Ilmu Hukum dan Sosial, 2024)
The responsibility of shareholders, known as the piercing the corporate veil doctrine, in the bankruptcy of a limited company based on Law Number 40 of 2007 is only limited to the share capital paid by shareholders to the company. The shareholder's responsibility for the shares paid up does not apply if proven; shareholders, whether directly or indirectly, in bad faith, use the limited liability company for personal interests, shareholders who are involved in unlawful behavior use the assets of the limited liability company for personal gain, which results in the assets of the limited liability company being reduced and insufficient to pay off the debts of the limited liability company. The General Meeting of Shareholders, hereinafter referred to as (GMS), is an organ of a limited liability company which has authority that is not delegated to the Board of Directors or the Board of Commissioners in carrying out its duties and authority. The duties and authorities of the GMS organs in the UUPT are; making changes to the articles of association, increasing the company's capital, reducing the company's capital, appointing directors, determining the amount of allowances for members of the board of directors, dismissing directors, appointing commissioners, determining the amount of honorarium salaries and allowances for commissioners, as well as appointing independent commissioners and dissolving the company.